Information technology in the age of emergency public health response. - Popovich, M.L (IEEE Engineering in medicine and biology magazine)
For over 20 years, our nation's public health system has continually struggled to combat ongoing and emerging public health threats and emergencies. Deadly threats have created considerable interest among healthcare providers, public health officials, state and local politicians, the Congress, and the President. As a consequence, substantial funding has been made available to federal, state, and local public health agencies to build a stronger, more vigilant public health system. Significant investment is being made to develop local and regional public health response plans, create robust information systems to support exchange of critical data and information, improve workforce competencies, and enhance communication systems needed to inform responders, the healthcare community, and the public. To succeed, public health agencies need a sophisticated and proven information technology framework that can be effectively applied to improve public health readiness. This article provides insight into the development of that framework, an integrated disease surveillance system for rapid detection, tracking, and managing of public health threats, within the context of the overall public health system